Theorizing the Role of Sex Educators in the Resistance and Reification of Epistemic Injustices Related to the Sexual Expression of People with Intellectual Disability. - Curtiss, Sarah L.; Stoffers, Melissa (Archives of Sexual Behavior, 2025)
People with intellectual disability face a variety of epistemic injustices—systems of knowledge and educational inequality—related to their access to sex education and perceptions of their sexuality. Sex educators are in a position to address these injustices; however, they may not be fully aware of their own epistemic ethics. Furthermore, there is little theoretical understanding of how sex educators provide instruction within an environment that exhibits hostility toward the sexual expression of those with intellectual disability. This grounded theory study of interviews with 58 people who taught sex education to people with intellectual disability sought to understand the role of educators in perpetuating and resisting epistemic injustice by utilizing sex education to either facilitate or restrict the sexual expression of people with disabilities. We identified four micro-contexts: centralizing capacity to consent, emphasizing risk, desexualizing (through) sex education, and acknowledging gender identity. In each micro-context, we explore mechanisms of how educators were either allied in support of autonomy (person-centered values, expertise, access to curricular resources, self-advocates as teachers and partners, subversiveness, and de-problematizing normative sexual behavior) or reified sexual stigmas (fear of sexual abuse and sexual perpetration, conscripting to asexuality, the paternalistic service system, and complex ethical dilemmas) in the context of hostility to sex education and sexual expression. These findings have implications for promoting prosocial sexual expression and access to sex education for people with intellectual disability.